A prospective comparison of growth patterns with radiomorphology in 232 lung metastases—basis for patient tailored resection planning? - Issa, Nomair; Arfanis, Elias; Hager, Thomas; Aigner, Clemens; Dietz-Terjung, Sarah; Theegarten, Dirk; Kühl, Hilmar; Welter, Stefan (Journal of Thoracic Disease, 2019)
Background: The histologic presence of aggressive local growth of pulmonary metastases is associated with an increased risk for local intrapulmonary recurrence after enucleation or wedge resection. Patient tailored resection planning is possible when morphologic pattern of aggressive growth could be identified based on preoperative CT scans. Methods: Radiomorphology and microscopic growth characteristics from 232 pulmonary metastases from 87 patients were prospectively compared for the presence or absence of aggressive patterns of local intrapulmonary dissemination. Results: Microscopic aggressive local growth was found: pleural involvement (18.5%), lymphatic invasion (6.9%), vascular invasion (7.3%), interstitial growth (38.4%), micro satellite nodules (24.5%), spread through air spaces (STAS) (13.4%), and a smooth, slightly blurred or irregular surface in 34.1%, 43.1% and 22.8%. The radiologic margin demarcation was smooth in 37.1%, blurred in 27.6% or irregular in 35.3% and spiculae were present in 26.3% of the lesions. The microscopic and radiologic description of the metastasis surface correlated well [correlation coefficient (CC) =0.75, P